Ages and metallicities of eight star clusters and their surrounding fields in the inner disc of the Large Magellanic Cloud - Geisler, Doug (2003)
We present Eashington system colour-magnitude diagramsfor 8 stars clusters and their surrounding fields which, with one exception, lie within the inner parts of the Large Magellanic Cloud (LMC) disc. Careful attention is paid to separating out the cluster and field star distributions. Ages and metallicities are then determined in a consistent manner for both populations in two different ways. We first compare the colour-magnitude diagrams (CMDs) with new theoretical isochrones in the Washington system. We also derive ages using the magnitude difference between the red clump and the turnoff, and derive metallicities by comparing the giant branches to standard calibrating clusters. For this latter mtallcitiy derivation, we present age-cdependent metallicity corrections for intermediate age clusters (IACs) based on the new isochrones. The two methods for both age and metallicity determination are in good agreement with each other. All clusters are found to be IACs 1-3 Gyr), with metallicities from -0.4 to -0.9. We find that the stellar population of each star cluster is generally quite similar to that of the field where it is embedded, sharing its mean age and metallicity. Combining the present sample with a revision of of Bica et al.. studied similarly, we find that our metallicities for IACs are intermediate in metallicity to those for clusters of similar age studied by Olsewski et al. and Beasley, Hoyle & Sharples. A combined age-metallicity relation is presented which shows that LMC clusters formed between 1-3 Gyr ago with a mean metallicity (-0.5 dex) and metallicity spread (0.23 dex) independent of age. Good agreement is found with the bursting model of pagel & Tautvaisiene. No evidence for a metallicity gradient is found.